Paradigma Pengembangan Kebudayaan Yang Qur'ani - Hambali, Gufron (ULUL ALBAB Jurnal Studi Islam, 2003)
Culture is the varieties of human actions in this world to change, to produce, and to develop by process. It is a result of the human’s art feeling which formed in a certain idea, activities, social system and artifacts. As the cultural creature, -human· always be creative to create the cultural innovative which based on a belief and an internal or external condition. These cultural phenomena are always various. In this modern period, the western culture is more dominant than other cultures. It can influence and assimilate with a certain nation’s culture, and gives the negative effect in the moral aspect and belief in the religion. Thus, this article describes about the Qur'anic forming culture based on the basic Islamic Theology can be  developed dynamically. AI-Qur 'an is the revelation of Allah, it becomes a way of life for Moslems and it always can answer the developing of Human’s  culture in the world.